2023
DOI: 10.1536/ihj.22-563
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically Improved Severe Pulmonary Arterial Hypertension Caused by Qing-Dai (Chinese Herbal Drug) for Ulcerative Colitis

Abstract: Pulmonary arterial hypertension (PAH) is a rare and fatal disease for which some causative drugs have been developed. Qing-Dai is a Chinese herbal drug that is sometimes used as a specific treatment for ulcerative colitis in Asia, including Japan. Here, we report a case of severe Qing-Dai-induced PAH. A 19-year-old woman who has been taking Qing-Dai for 8 months was admitted for exertional dyspnea. Her mean pulmonary artery pressure dramatically improved from 72 to 18 mmHg with Qing-Dai discontinuation and PAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In the same study, one case was reported where liver levels increased 10 times the upper limit of normal. Recently, many cases of pulmonary hypertension have been reported in patients taking green tea for UC [ 58 - 60 ]. These cases have a common rapid improvement after stopping taking IN.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, one case was reported where liver levels increased 10 times the upper limit of normal. Recently, many cases of pulmonary hypertension have been reported in patients taking green tea for UC [ 58 - 60 ]. These cases have a common rapid improvement after stopping taking IN.…”
Section: Discussionmentioning
confidence: 99%
“…Because BMI was reduced, we consider that Bofutsushosan was able to improve obesity. Although Seitai (Chinese name: Qing-Dai) was known as the crude drug that had therapeutic effects for ulcerative colitis, which may be associated with LSRDs, it improved the pulmonary arterial hypertension of the patients with ulcerative colitis [ 107 , 108 ]. Kampo medicines may inhibit the generation of intracellular AGEs, block the extracellular AGEs-RAGE/TRL4 axis, and suppress phenotypes via AGEs-RAGE/TRL4 axis signaling.…”
Section: Effects Of Kampo Medicines On Intra- and Extracellular Agesmentioning
confidence: 99%
“…The report by Kubota, et al 1) of a patient with severe Qing-Dai-induced pulmonary arterial hypertension (PAH) underscores a need to reclassify the relationship between PAH and certain drugs and toxins, first introduced at the 6th World Symposium on Pulmonary Hypertension in 2018. 2) The current classification notes that indirubin (Chinese herb Qing-Dai) is possibly related to PAH.…”
Section: To the Editormentioning
confidence: 99%